Effects of Mobile Instant Messaging Towards Malaysian Gen-Y Impulse Buying - Lee, Yi Yong (2020)
There is a growing study of mobile advertising of its influence in determining consumer’s impulsiveness. Yet, there is limited attention has been paid to examine the impact of mobile purchasing interaction in determining consumer’s impulse buying urges. The current study integrates Stimulus–Organism–Response theory and Parasocial Interaction theory to develop the research model. The research framework was established with impulse buying tendency (IBT), parasocial interaction (PSI), normative evaluation (NE), positive affect (PA) as predictors, and urge to buy impulsively during the purchase interaction with the sellers on mobile instant messaging (IM) as the dependent variable. This study also attempts to investigate the mediating effect of positive affect (PA). The sample for this study consisted of 245 respondents with the following characteristics: Malaysian who born between the years 1980 to 2000; and use IM for purchase interaction with the sellers. The structural model of this study was analysed using structural equation modeling conducted in Smart PLS 3.0. IBT, NE, and PSI positively influenced PA (mediator) during the purchase interaction with the sellers on IM. IBT, NE, and PA positively influenced UB. PA mediated the relationship between the PSI and UB as well as the relationship between IBT and UB. PA did not mediate the relationship between NE and UB. Given the prevalence of impulse purchasing and its importance to businesses’ profit, thus, this study provides practical implications for the retailers or sellers to determine the antecedents of consumers’ impulse purchase urges during the purchase interaction with the sellers on IM.